Pathologies of acute interstitial pneumonia in feedlot cattle - Valles, J. A.; Apley, Michael D.; Reinhardt, Christopher D.; Bartle, Steven J.; Thomson, Daniel U. (My University, 2016)
Acute Interstitial Pneumonia (AIP) is a costly issue that affects feedlot cattle. Research has yet to elucidate the etiology of AIP; therefore a case-control study was conducted to evaluate possible management and physiological factors that contribute to AIP in feedlot cattle. The experiment was conducted during the summer of 2011 in a commercial feedyard in Kansas. Animals exhibiting clinical signs of AIP and a control animal from the same pen were selected for ante-mortem examination. Post-mortem AIP cases were also selected for additional examination. Ante-mortem measurements included rumen gas cap hydrogen sulfide and pH, rectal temperature and body weight. Post-mortem examination added histological examination of lung tissue. Rectal temperature was greater in the AIP cattle (40.6±0.16°C) than controls (39.7±0.16°C; p<0.001). Body weight (499±56 Vs. 506±60 kg), hydrogen sulfide (136±133 vs. 269.8±311 ppm) and rumen pH (6.4±0.5 Vs. 6.2±0.6) were similar between AIP and control cattle (p>0.10). Post-mortem rumen pH values were 6.3±0.4 and 5.7±0.6 for AIP and control cattle, respectively. Histological evaluation of lung samples showed that bronchiolitis was present in about 90% of the cattle affected with AIP. About 75% of the cattle with AIP also had bronchopneumonia. No relationships between feed intake patterns, or serum amylase or lipase levels were noted between treatments (p>0.20). This study generally confirms that AIP tends to occur more in heifers relative to steers, occurs in cattle at heavier weights or later in the feeding period and tends to be associated pathologically with bronchio’ litis and bronchopneumonia. The lack of differences in rumen measures and the feed intake data between AIP and control cattle suggest that feed intake patterns and rumen fermentation may not impact AIP in feedlot cattle and that it may be more directly related to bronchiolitis/bronchopneumonia due to chronic irritation or infection. © 2016 Jose A. Valles, Michael D. Apley, Chris D. Reinhardt, Steven J. Bartle and Daniel U. Thomson.
Citation: Valles, J. A., Apley, M. D., Reinhardt, C. D., Bartle, S. J., & Thomson, D. U. (2016). Pathologies of acute interstitial pneumonia in feedlot cattle. American Journal of Animal and Veterinary Sciences, 11(1), 1-7. doi:10.3844/ajavsp.2016.1.7
Keywords: Acute Interstitial Pneumonia; Feedlot Cattle; Lung Lesions